2020
DOI: 10.3389/fcell.2020.00623
|View full text |Cite
|
Sign up to set email alerts
|

Synonymous Mutations of Porcine Igf1r Extracellular Domain Affect Differentiation and Mineralization in MC3T3-E1 Cells

Abstract: Owing to the wide application of miniature pigs in biomedicine, the formation mechanism of its short stature must be elucidated. The insulin-like growth factor 1 receptor (IGF-1R), which receives signals through the extracellular domain (ECD) binding with ligands, is crucial in regulating cell growth and bone matrix mineralization. In this study, two haplotypes of Igf1r with four synonymous mutations in the coding sequences of IGF-1R ECD between large pigs (LP) and Bama pigs (BM) were stably expressed in the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…We suspected that let-7e-5p likely plays a vital role in regulating the differentiation of osteoblasts and then participates in bone formation. The activity of ALP and the expression levels of genes related to osteogenic differentiation ( RUNX2 , OPN , OCN , and OSX ) regulate osteoblast differentiation and bone formation in growing bones; the expression levels of the above genes gradually increase during osteoblast differentiation and are important factors for evaluating cell differentiation ( Wang C. et al, 2020 ; Wei et al, 2020 ). Similar to the results of previous works, our results for the transfection of the let-7e-5p mimic confirmed that let-7e-5p enhanced the osteoblast differentiation potential by increasing the ALP activity ( Xi et al, 2016 ) and regulating RUNX2 , OCN , OPN , and OSX expression in MC3T3-E1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We suspected that let-7e-5p likely plays a vital role in regulating the differentiation of osteoblasts and then participates in bone formation. The activity of ALP and the expression levels of genes related to osteogenic differentiation ( RUNX2 , OPN , OCN , and OSX ) regulate osteoblast differentiation and bone formation in growing bones; the expression levels of the above genes gradually increase during osteoblast differentiation and are important factors for evaluating cell differentiation ( Wang C. et al, 2020 ; Wei et al, 2020 ). Similar to the results of previous works, our results for the transfection of the let-7e-5p mimic confirmed that let-7e-5p enhanced the osteoblast differentiation potential by increasing the ALP activity ( Xi et al, 2016 ) and regulating RUNX2 , OCN , OPN , and OSX expression in MC3T3-E1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The MC3T3-E1 cells were cultured in Dulbecco’s minimal essential medium (DMEM, Sigma, United States) supplemented with 10% fetal bovine serum (FBS, Hyclone, United States) and 1% streptomycin/penicillin (Gibco, United States) at 37°C in a humidified 5% CO 2 incubator. The differentiation medium contained 10 mmol/L β-glycerophosphate (Sigma, United States), 50 mg/mL ascorbic acid, and 10 nM dexamethasone (Sigma, United States) ( Wang C. et al, 2020 ; Wei et al, 2020 ). HEK293T cells were cultured in DMEM (Hyclone, China) supplemented with 10% FBS and 1% penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations